Pengelolaan Kompetensi Aparatur Sipil Negara(ASN) Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manausia (BKPSDM) Kabupaten Bantaeng - Idris, Erwin Ramadansyah; Adys, Abdul Kadir; Abdi, Abdi (Universitas Muhammadiyah Makassar, 2020)
This study aimed to find out the preventive and repressive supervision of the Financial Services Authority (Otoritas Jasa Keuangan – “OJK”) to Government-owned Banks in Makassar City. The method used in this study was descriptive qualitative with five informants. The data collection techniques included observation, interviews and documentation. The results of the study showed that the implementation of preventive supervision of financial services authorities (Otoritas Jasa Keuangan – “OJK”) in supervising Makassar City government banks regarding socialization, work plans, and resources that had run optimally. Also, Repressive supervision of the audit post and inspection had run maximally. Thus, the result of this study showed that the supervision carried out by the financial services authority run maximally.